Techno-economic analysis on a small-scale organic Rankine cycle with improved thermal driven pump. (1st August 2020) - Jiang, L.; Wang, R.Q.; Roskilly, A.P.
Highlights: Organic Rankine cycle (ORC) with improved thermal driven pump (TDP) is presented. The up-limit cycle thermal efficiency is explored by using discrete dividing method. Mass ratio of reactor and pump efficiency are evaluated for the real applications. ORC with improved TDP may be a substitute to conventional ORC under suitable conditions. Abstract: Thermal driven pump is usually defined as a thermodynamic way which plays a similar role to replace common electricity driven pump. In this paper, a concept of improved thermal driven pump series is introduced to small-scale organic Rankine cycle and the up-limit thermal efficiency is explored by using discrete dividing method. Results indicate that power outputs of organic Rankine cycle by using thermal driven pump V2 range from 158.8 W to 343.1 W which are improved by up to 73.5% when compared with those using previous type V1 . Energy and exergy efficiencies using improved type V2 and V3 increase from 0.018 to 0.043 and from 0.145 to 0.246, respectively. The largest increment could reach 40.5% and the highest value could account for 85% of the up-limit performance. Influencing factors i.e. mass ratio and pump efficiency are defined to further evaluate the performance in the possible applications. One remarkable inspiration is that organic Rankine cycle by using improved thermal driven pump may be an alternative solution to conventional type which could achieve the better techno-economic performance only under the conditions of dividing number smaller than 4 and the scale less than 10 kW.